Direct observation of morphological development during the spin‐coating of polystyrene–poly(methyl methacrylate) polymer blends. Issue 11 (27th March 2013) - Toolan, Daniel T. W.; Haq, Ehtsham ul; Dunbar, Alan; Ebbens, Stephen; Clarke, Nigel; Topham, Paul D.; Howse, Jonathan R.
ABSTRACT We present results of the direct observation, in real‐space, of the phase separation of high molecular weight polystyrene and poly(methyl methacrylate) from ortho‐xylene using our newly developed technique of high speed stroboscopic interference microscopy. Taking a fixed concentration (3 wt % in o‐xylene) at a fixed composition (1:4 by weight) and by varying the rotational rate during the spin‐coating process, we are able to observe the formation of a range of phase separated bicontinuous morphologies of differing length‐scales. Importantly, we are able to show that the mechanism by which the final phase separated structure is formed is through domain coarsening when rich in solvent, before vitrification occurs and fixes the phase separated structure. The ability to directly observe morphological development offers a route toward controlling the length‐scale of the final morphology through process control and in situ feedback, from a single stock solution. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B Polym. Phys. 2013, 51, 875–881